2000
DOI: 10.2170/jjphysiol.50.273
|View full text |Cite
|
Sign up to set email alerts
|

The Biomechanic Origin of Sprint Performance Enhancement after One-Week Creatine Supplementation.

Abstract: Creatine (Cr) is an endogenous as well as an exogenous compound related with high-energy metabolism [1,2]. During muscular exercise, ATP is directly used for mechanical contractions of actin and myosin filaments. The fastest anaerobic metabolic pathway to regenerate ATP is the utilization of phosphocreatine (PCr). However, the total pool of PCr is limited. The ingestion of exogenous Cr consequently increases intracellular Cr and PCr concentrations [3,4]. This increase could therefore theoretically improve mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In other words, if anything can be indicated from the current results, it is that step time is reduced after training (14,17). These observations are in agreement with the observed improvement of sprint performance with creatine supplements and associated increase in step frequency (18). Otherwise, the ability to activate muscle fully at high contraction velocities may have been enhanced (4).…”
Section: Discussionsupporting
confidence: 86%
“…In other words, if anything can be indicated from the current results, it is that step time is reduced after training (14,17). These observations are in agreement with the observed improvement of sprint performance with creatine supplements and associated increase in step frequency (18). Otherwise, the ability to activate muscle fully at high contraction velocities may have been enhanced (4).…”
Section: Discussionsupporting
confidence: 86%
“…The participants who took 20 gr creatine daily performed significantly better in sprints compared to controls. Investigating the biomechanical source of creatine loading on sprint performance, Schedel, Terrier, Schutz, (2000) discovered that there was an increase in step frequency of the athletes taking creatine, which might stem from the shortening in muscle contraction and relaxation occurred as a result of intense intracellular phosphocreatine (pc) (Oztasyonar, Atasever, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Given that some individuals experience a small increase in body mass following Cr ingestion, it is could be theorized that Cr supplementation might alter running mechanics and consequently be ergolytic in weight bearing activities. In fact, Schedel et al (2000) reported that Cr supplementation (20 g/d for 7 d) increased body mass (0.8 kg), running speed, and stride frequency, but not stride length. However, Cox et al (2002) reported improved 20 m sprint time and agility run performance despite an increase in body mass (0.8 kg).…”
Section: Runningmentioning
confidence: 98%